Antibody-dependent cellular cytotoxicity and neutralizing activity in sera of HIV-1-infected mothers and their children. - Broliden, K (1993)
The prognostic and protective role of antibodies mediating cellular cytotoxicity (ADCC) and neutralization was evaluated in sera of HIV-1-infected mothers and their consecutively followed children. The presence and titres of ADCC mediating and/or neutralizing antibodies in maternal sera did not predict HIV-1 infection in their respective children. No significant difference in the sera from the children was seen when comparing the presence of neutralizing antibodies between the uninfected and infected children. Stratification of the infected group according to clinical status revealed differences. Only one of 24 AIDS patients had a high neutralizing titre against IIIB. Four patients had a very low titre and the remaining had no detectable neutralizing antibodies at all. In contrast, 10/17 infected non-AIDS children had neutralizing antibodies. Similarly, no significant difference was seen when comparing the presence of ADCC-mediating antibodies between the uninfected and the infected group of children. However, a significantly higher frequency of ADCC was seen in the seropositive non-AIDS children compared with the AIDS children. This study clearly shows that the presence of antibodies mediating ADCC and neutralization in infected children, 0-2 years old, is associated with a better clinical status and delayed disease progression.